URGENSI SUMBER DAN MEDIA PEMBELAJARAN LABORATORIUM PADA SISWA MADRASAH ALIYAH - Aulya Zahwatun Nisa (UNZAH Genggong, 2022)
Learning resources and media are currently very helpful in the learning process. One that can be used as a source and learning media effectively is the laboratory. The laboratory has a very important role in learning at the senior secondary level such as Madrasah Aliyah. The purpose of writing this article is to determine the urgency of laboratory learning media and sources as well as the role of laboratories in madrasah aliyah. This research uses a qualitative approach. The method used is the case study method with descriptive analysis techniques. Data collection techniques in this study are observation and interviews. This research was conducted at Madrasah Aliyah Nahdlatul Ulama Kepuharjo Karangploso. The application of practical methods / scientific methods to Islamic madrasah learning requires a laboratory as a means or a place to carry out practical activities. The use of laboratories or practical activities is part of the teaching and learning process. In addition, laboratories can help students to better understand something that is conveyed by educators. Moreover, the use of laboratories for students at the madrasah aliyah level, which later students can use various laboratory facilities for practical activities according to the subject directly. Thus, the laboratory has an important role as a source and medium of learning so that teaching and learning practicum activities run well. Keyword: Urgency of learning resources, Laboratory, Madrasah aliyah